The Concept of Child-Free Lifestyle in the Context of Maqasid Shariah: Ethical Considerations and Social Implications - Ahmad Maulidizen; Abdul Haris Muchtar; Atikah Salimah; Risman Nugraha (Journal of Islamic Law and Legal Studies, 2024)
This research aims to explore the concept of the child-free lifestyle within the framework of Maqasid Shariah, focusing on the ethical considerations and social implications associated with such a decision. The study seeks to understand how Islamic principles and objectives—preserving faith, life, intellect, progeny, and wealth—interact with the modern choice of living child-free. By utilizing a qualitative library research approach, the study analyzes various Islamic texts, scholarly opinions, and contemporary discussions on reproductive choices, providing an in-depth understanding of how the child-free lifestyle aligns with Maqasid Shariah. The findings reveal that while Maqasid Shariah emphasizes the importance of procreation for the continuation of society, it also recognizes individual autonomy, personal choice, and the preservation of well-being. The study concludes that, from a Shariah perspective, the child-free lifestyle may be considered ethically permissible under specific circumstances, especially when it aligns with the overall well-being and goals of an individual or couple. The implications of this research are significant for policymakers, religious scholars, and society at large, as it encourages a nuanced understanding of reproductive choices, personal freedom, and societal responsibilities in contemporary Islamic contexts.